2021
DOI: 10.1186/s12936-021-03998-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting countries to achieve their malaria elimination goals: the WHO E-2020 initiative

Abstract: Background Malaria causes more than 200 million cases of illness and 400,000 deaths each year across 90 countries. The World Health Organization (WHO) set a goal for 35 countries to eliminate malaria by 2030, with an intermediate milestone of 10 countries by 2020. In 2017, the WHO established the Elimination-2020 (E-2020) initiative to help countries achieve their malaria elimination goals and included 21 countries with the potential to eliminate malaria by 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Three indigenous cases were then reported in that area. 6 Similarly in Bhutan, in 2020 after COVID-19 emerged, the country reported an outbreak of 22 indigenous malaria cases in the bordering district of Sarpang. This was partly attributed to the delays in delivery of malaria prevention interventions due to the pandemic.…”
Section: Setback On E2020-the Experience Of Bhutan and Timor-lestementioning
confidence: 99%
See 3 more Smart Citations
“…Three indigenous cases were then reported in that area. 6 Similarly in Bhutan, in 2020 after COVID-19 emerged, the country reported an outbreak of 22 indigenous malaria cases in the bordering district of Sarpang. This was partly attributed to the delays in delivery of malaria prevention interventions due to the pandemic.…”
Section: Setback On E2020-the Experience Of Bhutan and Timor-lestementioning
confidence: 99%
“…This was partly attributed to the delays in delivery of malaria prevention interventions due to the pandemic. 6 , 10 In 2019, Bhutan reported only two indigenous cases. 8 Greater risk of imported cases from high burden neighbour countries : The Sarpang district of Bhutan is on the border with India.…”
Section: Setback On E2020-the Experience Of Bhutan and Timor-lestementioning
confidence: 99%
See 2 more Smart Citations
“…Many national malaria programmes have recently set time-bound goals to eliminate malaria [ 1 ], but it is currently unclear what timelines such accomplishments will truly require. Of 21 countries identified in 2016 as potential contenders for elimination by 2020 [ 2 ], only seven succeeded in interrupting transmission by the deadline, while the elimination goal for all others was shifted back another five years [ 3 ]. One investigation found that targets set by sub-Saharan African malaria programmes generally were more aligned with global goals than local contexts, and of 135 targets set, only four were achieved [ 4 ].…”
Section: Introductionmentioning
confidence: 99%